Solidaritas Antaragama dalam Membangun Resiliensi Masyarakat di Era Pandemi Covid-19 di Kota Manado - Nelwan, Gerry (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2022)
The Covid-19 Pandemic has had a broad impact on society. Since one aspect of it is the economy, the government comes up with an effort to help society. Besides the government, religion also moves to embrace its adherents who feel the impact of the COVID-19 Pandemic and even appears in the plural society in Manado city. This research aims to show that religion has taken its role in helping society in the Covid-19 Pandemic Era. Religion also stands together with society to overcome many challenges caused by the Covid-19 Pandemic. This research also continues to develop and fill the gap of some previous research regarding the topic. That is the effort of religion to build a strong society while facing the COVID-19 Pandemic. This research uses the qualitative-descriptive method with a library study. In this regard, the researcher would collect and analyze scientific literature, books, newspapers, and related documents. The situation in Manado City depicts the role of religion in helping society in the Covid-19 Pandemic Era. Various interreligious organizations in Manado City communally join the movement to help the people being affected by the Covid-19 Pandemic. The involvement of religion has become an important part of building a strong society to face the COVID-19 Pandemic, especially in Manado City. Solidarity built from the shared awareness among religions could be an example for other regions in Indonesia.